PERAN PEMUDA BERTAUHID DALAM MENCEGAH KORUPSI - Mardana, Tio; Cecep Padlu Rohman; Agung Rohmadi; Hamzah Abdulah Let-let; Muhamad Syahrul Syamsudin; Muhammad Daffa Akbar (DE’RECHTSSTAAT, 2023)
Efforts to eradicate corruption in Indonesia have been carried out in various ways, but until now corruption still occurs. Based on the 2021 Corruption Perception Index (CPI), Indonesia is ranked 96th out of 180 countries. This score is worse than the IPK score in 2020 where Indonesia is ranked 102 out of 180 countries. This proves that Indonesia has not been effective in preventing or eradicating corruption, which is why this journal was created, which hopefully will become a shield and a sword for the younger generation who uphold the values of Pancasila, namely monotheism in preventing and eradicating corruption. Results: The role of monotheistic youth in preventing acts of corruption. Youth have several important roles that can be played in the fight against corruption. First, the anti-corruption agency. The natural capital possessed by these young people should be able to be embodied in anti-corruption attitudes and principles.